Correlation of Multidector 64 Ct Pulmonary Angiography and Well’s Clinical Score in Pulmonary Embolism (Indian Journal of Public Health Research & Development, 2020)
Objective: To correlate the findings of 64 MDCT Pulmonary angiography & Well’s clinical scoring systemin cases of pulmonary embolismPatients and Method: The study was done between April 2010 to may 2012, 50 patients with suspectedclinical pulmonary embolism underwent 64- Multislice CT pulmonary angiography. CT angiography wasused in examination and evaluation for patients suspected of having PE with Correlation with clinical Well’sscoring system.Results: Images from “41 of 50” thoracic CT pulmonary angiography examination revealed clots withinpulmonary arteries, which equals a prevalence of PE of 82%, overall (10 of 41 at pulmonary trunk, 8 of 41at segmental pulmonary arteries and 18 of 41 at subsegmental pulmonary arteries, of 24%, 19.5% and 43.9%respectively, 5 of 41 at multiple central/segmental and segmental/subsegmental arteries of 12%)Patients with low Well’s score probability confirmed to have very low incidence of pulmonary embolism,while patients with both medium & high Well’s score probability having high incidence of pulmonaryembolism in CT Pulmonary angiography in our studyConclusion: Correlation of Both 64-MDCT Pulmonary Angiography & Clinical Scoring Well’s systemsshowing high relation in-between, considering that group having low clinical probability to have PE,
Keywords: MDCT, Angiography, Pulmonary